Analytical modeling of carbon nanotube transistor based biosensor for glucose detection - Hosseingholipourasl, Ali (2014)
The industry in sensory devices, nowadays, has become overflowed with the development of carbon nanotubes based sensor. So far, wide ranges of potential and practical applications of CNTs have been reported, including chemical sensors electronic devices and so on. CNT possess enhanced electron transfer property when used as electrodes in electrochemical reactions and serves as a good solid support for easy protein immobilization that retains their native activity for use as potential biosensors. The determination of glucose levels using biosensors, particularly in the medical diagnostics and food industries, is gaining mass appeal. The glucose biosensors detect the glucose molecule by catalyzing glucose to the gluconic acid and H2O2 in the presence of oxygen. In this study, a single-wall carbon nanotube field-effect transistor (SWCNT FET) biosensor for glucose detection is analytically modelled. In the proposed model, the glucose concentration is presented as a function of gate voltage. Subsequently, the proposed model is compared with existing experimental data. A good consensus between the model and the experimental data is reported. The simulated data demonstrate that the analytical model can be employed with an electrochemical glucose sensor to predict the behavior of the sensing mechanism in biosensors.